2015
DOI: 10.1038/jcbfm.2015.52
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lipocalin-2 in Brain Injury after Intracerebral Hemorrhage

Abstract: Lipocalin-2 (LCN2) is a siderophore-binding protein involved in cellular iron transport and neuroinflammation. Both iron and inflammation are involved in brain injury after intracerebral hemorrhage (ICH) and this study examined the role of LCN2 in such injury. Male adult C57BL/6 wild-type (WT) or LCN2-deficient (LCN2 − / − ) mice had an intracerebral injection of autologous blood or FeCl 2 . Control animals had a sham operation or saline injection. T2-weighted magnetic resonance imaging and behavioral tests we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 40 publications
6
53
0
Order By: Relevance
“…Most of the LCN2-positive cells were astrocytes. This finding is consistent with previous reports 9, 11, 19, 20 , although neurons, microglia, and endothelial cells can also express LCN2 12, 21 . Our data also found that thrombin results in a significant neutrophil infiltration which may also contribute to increased brain LCN2 levels (LCN2 is also known as neutrophil gelatinase-associated lipocalin).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Most of the LCN2-positive cells were astrocytes. This finding is consistent with previous reports 9, 11, 19, 20 , although neurons, microglia, and endothelial cells can also express LCN2 12, 21 . Our data also found that thrombin results in a significant neutrophil infiltration which may also contribute to increased brain LCN2 levels (LCN2 is also known as neutrophil gelatinase-associated lipocalin).…”
Section: Discussionsupporting
confidence: 93%
“…Thrombin and iron are two major factors causing brain damage after ICH 1 . Our data have shown that LCN2 has a role in iron-mediated brain damage 12 . It is still unclear whether LCN2 has a role in thrombin-induced brain damage.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations